Antenatal preparation as care: birth stories and collective learning at work - De Quattro, Leah (Frontiers in Global Women's Health, 2025)
Distressing and harmful birth experiences are the norm even in well-resourced countries, and conventional antenatal education struggles to adequately prepare birthing people. Drawing on previous research in support of participant-led antenatal education, a recent UK-based ethnographic study asks how birthing people use collective practices to produce birth knowledge. Data comes from participant observation at 24 antenatal sessions (n = 201) including conventional classes and community-based groups, plus 5 interviews with session leaders. The researcher analysed data using a novel application of template analysis, framed by feminist technoscience, ethnography and socio-narratology. Findings show how group-led sessions, storytelling and other collective knowledge practices take care of birthing people. Several facets of care emerge from this inquiry, such as materiality, emotionality, working athwart dominant narratives and creating “care-full” absences or spaces. Excerpts from antenatal preparation sessions specifically demonstrate various approaches to knowledge working – and caring – in practice. A focus on real-life examples and implications ensures findings are useful and relevant for birthing women, midwives, antenatal educators, institutions, policymakers and more.